Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board - Part IX.- Newsprint Grade Mechanical Pulp From Sterculia campanulata (Papita) - Virmani, K. C. (Indian Forester, 1952)
Laboratory experiments on the production of mechanical pulps from Sterculia campanulata (papita) are described. Standard pulp sheets were prepared from 100% mechanical pulp from this species and from a mixture of 70% mechanical pulp and 30% bamboo bleached chemical pulp. The strength properties of the standard sheets prepared from the mechanical pulp produced under suitable conditions have shown that this wood is a promising raw material for the production of newsprint. The colour of the pulp is also suitable for newsprint. This species is available in the Andamans and the wood is used in the match industry in Calcutta.